Pengaruh Keselamatan Kerja, Lingkungan Kerja Dan Komunikasi Kerja Terhadap Kinerja Karyawan Pada PT. Kutai Timber Indonesia Kota Probolinggo - Nurul Hasanah; Muhammad Syarif Hidayatullah Elmas; Umi Rahma Dhany (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at PT. Kutai Timber Indonesia, Probolinggo City with the aim of determining the effect of occupational safety, work environment and work communication on employee performance. The type of research used is quantitative research with an associative approach. The population is employees of PT. Kutai Timber Indonesia, Probolinggo City with a sample of 36 respondents and the sampling technique using saturated sampling technique. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, determination test, partial test and simultaneous test. The results of the study indicate that occupational safety, work environment and work communication partially have a significant effect on employee performance.